2011
DOI: 10.1094/pdis-12-10-0919
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Cryptovalsa ampelina and Eutypella leprosa Associated with Grapevine Trunk Diseases in Chile

Abstract: Trunk diseases (TD) of grapevines (Vitis vinifera L.) have increased considerably in Chile with an incidence of more than 25% found in ≥7-year-old vineyards. Only species of Botryosphaeriaceae, Phaeoacremonium, and Phaeomoniella were associated with TD in Chile (1,2). From 2009 to 2010, isolations were made from the grapevines ‘Cabernet Sauvignon’, ‘Carmenere’, ‘Flame Seedless’, and ‘Pinot Noir’ collected in central Chile (33°27′ to 34°39′S, 71°17′ to 71°33′W). These grapevines showed cankers and vascular necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In this sense, several works have evaluated the effect of early versus late pruning on the level of infection of pruning wounds, where late pruning (February-March) can reduce the risk of infection to P. chlamydospora , because early pruning (December-January) coincides with the peak of spore release and the presence of the first rains of the season that generally occur in California ( Eskalen and Gubler, 2001 ). Similarly, these results were also found with E. lata and P. chlamydospora , where early pruning inoculations showed higher levels of spurs infected in France ( Chapuis et al., 1998 ) and Italy ( Serra et al., 2008 ), respectively. This is in contrast to the results obtained by Luque et al.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In this sense, several works have evaluated the effect of early versus late pruning on the level of infection of pruning wounds, where late pruning (February-March) can reduce the risk of infection to P. chlamydospora , because early pruning (December-January) coincides with the peak of spore release and the presence of the first rains of the season that generally occur in California ( Eskalen and Gubler, 2001 ). Similarly, these results were also found with E. lata and P. chlamydospora , where early pruning inoculations showed higher levels of spurs infected in France ( Chapuis et al., 1998 ) and Italy ( Serra et al., 2008 ), respectively. This is in contrast to the results obtained by Luque et al.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies performed in vineyards with inoculation of fungal trunk pathogens, including Eutypa lata , Botryosphaeriaceae, and P. chlamydospora on pruning wounds, have shown that the susceptibility was highest to infection when the inoculation was done on fresh pruning wounds (the first two weeks), but the susceptibility decreased on the wounds when the time between pruning wounds and inoculation increased ( van Niekerk et al., 2011 ; Úrbez-Torres and Gubler, 2011 ; Elena and Luque, 2016 ). Moreover, according to studies on the grapevine, the pruning wounds inoculated with P. chlamydospora can be susceptible for a period extended up to 4 to 16 weeks after pruning from vineyards in California ( Eskalen et al., 2007 ), France ( Chapuis et al., 1998 ), Italy ( Serra et al., 2008 ), South Africa ( van Niekerk et al., 2011 ) and Spain ( Elena and Luque, 2016 ). For the development of a strategy in the management of the GTDs, studies about the duration of pruning wounds are important to elucidate aspects such as time for protection with fungicides and biological agents according to the susceptibility of pruning wounds.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the co-occurrence of P. viticola and E. lata has been hypothesized in explaining variation in the development of grapevine dieback (Péros et al, 1999). The fungus C. ampelina, isolated only from one vine sample, has also been associated with grapevine decline in Spain and Chile (Martin et al, 2009 ;Díaz et al, 2011), although it does not appear to be a major pathogen because of its low virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new species have been described in Australia ( Eutypella microtheca , Eutypella citricola and Diatrypella vulgaris ; Trouillas et al. , 2011) and in Chile ( Eutypella leprosa ; Diaz et al. , 2011).…”
Section: Eutypa Diebackmentioning
confidence: 99%